Survival And Heat Resistance Of Salmonella Enterica Serovar Weltevreden In Blanched Vegetables At Different Temperatures - Ahmad, Nor Afiqah (Universiti Sains Malaysia, 2020)
Consumption of fresh vegetables that undergo minimally processed without heat treatment is quite risky as the vegetables also contain indigenous microorganisms and other pathogens such as Salmonella that may cause food poisoning. Blanching is the heat treatment applied to the vegetables to reduce and eliminate the microorganism that presents on the vegetables. However, insufficient heat treatment during blanching may cause the microorganism able to survive. This study was performed in order to determine the heat resistance of Salmonella Weltevreden, its survival after blanched in different vegetables used which were the bean sprout, and water spinach samples with different temperatures at 70 °C, 75 °C, 85 °C and 100 °C. Survivor of Salmonella Weltevreden and the D-values can be determined after blanched. The vegetable samples used were inoculated with the Salmonella Weltevreden inoculum before undergoes the blanching process according to specific temperatures and interval times which were 15, 30, 60, 90 and 120 secs at both 70 °C and 75 °C while 5, 10, 15, 20, 25, 30 and 60 secs at both 85 °C and 100 °C. The results in this research shown that the survivor population of Salmonella Weltevreden after blanched at all temperatures becomes decreased until no more survivor population can be observed when both of interval times and temperatures used during blanching was increasing. Besides, the D-value achieved for bean sprout samples after blanching at 70 °C, 75 °C, and 85 °C and 100 °C were 25 secs, 14 secs, 10 secs and lastly 9 secs respectively.